Study and Analysis of Fundamental Transportation Problems in the City of Yerevan With the Purpose of Improvement - Sargsyan, Arman (Scientific Papers of National University of Architecture and Construction of Armenia, 2024)
The article examines the relationship between the physical and technical (intensity, density, speed) parameters of traffic flows on the Yerevan road network (RN). In fact, the traffic light control system currently in place does not prevent traffic jams in the conditions of existing traffic flows. Automated flexible traffic management systems are considered to be one of the ways to solve the problem, which require in-depth study of traffic flow assessment indicators, as well as investment of significant financial resources in technical equipment. Due to the disproportionate growth of roads and vehicles, the structures involved in the organization and control of traffic are forced to look for new methods and ways to solve the problem․